POLICY ON INDUSTRIAL MINERAL RESOURCE MANAGEMENT IN FRAMEWORK OF ELIMINATING DEPENDENCE ON IMPORT - DARSA PERMANA (Puslitbang tekMIRA, 2010)
Indonesia is one of the countries in the world that has abundant industrial mineral resource. Known as an exporter, Indonesia in fact also becomes an importer of various industrial minerals in a big and increasing amount from year to year. This is an apprehensive condition considering the negative impact given to the economy due to the absorption of the country’s foreign exchange. It also causes higher dependence on imported material and decreasing job opportunity for the people. Actually, industrial mineral mining does not need high technology and big investment; it is also of low risk. The problem is that the import rate is stagnantly high and it is caused especially by factors of unwise policy and conflict of interest from decision makers. The problem solution has to be derived around the issue. The issuance of Law No. 4 Year 2009 on Mineral and Coal Mining is expected to become the critical moment for reforming the policy and related regulations.